Protective role for C3aR in experimental chronic pyelonephritis. Issue 11 (17th October 2022) - Zhao, Shu‐Juan; Wu, Kun‐Yi; Min, Xiao‐Yun; Wang, Chun‐Xuan; Cao, Bo; Ma, Ning; Yang, Xue‐Ling; Zhu, Zhuo‐Ran; Fu, Rong‐Guo; Zhou, Wuding; Yang, Ju‐Rong; Li, Ke
Abstract: Emerging evidence suggest that C3aR plays important roles in homeostasis, host defense and disease. Although it is known that C3aR is protective in several models of acute bacterial infections, the role for C3aR in chronic infection is largely unknown. Here we show that C3aR is protective in experimental chronic pyelonephritis. Global C3aR deficient ( C3ar −/− ) mice had higher renal bacterial load, more pronounced renal histological lesions, increased renal apoptotic cell accumulation, tissue inflammation and extracellular matrix deposition following renal infection with uropathogenic E. coli (UPEC) strain IH11128, compared to WT control mice. Myeloid C3aR deficient ( Lyz2‐C3ar −/− ) mice exhibited a similar disease phenotype to global C3ar −/− mice. Pharmacological treatment with a C3aR agonist reduced disease severity in experimental chronic pyelonephritis. Furthermore, macrophages of C3ar −/− mice exhibited impaired ability to phagocytose UPEC. Our data clearly demonstrate a protective role for C3aR against experimental chronic pyelonephritis, macrophage C3aR plays a major role in the protection, and C3aR is necessary for phagocytosis of UPEC by macrophages. Our observation that C3aR agonist curtailed the pathology suggests a therapeutic potential for activation of C3aR in chronic infection.